Results of a double-blind, placebo-controlled pharmacotherapy trial in alcoholism conducted in Germany and comparison with the US COMBINE study - Mann, Karl; Leménager, Tagrid; Hoffmann, Sabine; Reinhard, Iris; Hermann, Derik; Wellek, Stefan; Kiefer, Falk (Addiction biology, 2013)
The results of placebo-controlled trials (RCTs) with acamprosate or naltrexone vary substantially. Those differences have been attributed to differing patient characteristics, recruitment strategies, treatment settings and remuneration systems. We tested these assumptions by comparing a new double-blind, placebo-controlled randomized trial conducted in Germany (called PREDICT Study) with data from the US COMBINE Study. PREDICT was designed according to the protocol of the COMBINE Study. A total of 426 alcohol-dependent patients were compared to 459 COMBINE Study patients corresponding to the treatment cells in PREDICT. All patients received acamprosate, naltrexone or placebo for 3 months (PREDICT) or 4 months (COMBINE). Biweekly manualized ‘medical management’ to enhance compliance was delivered in both studies. Time until the first occurrence of heavy drinking was the main outcome measure. PREDICT found neither acamprosate nor naltrexone to supply any additional benefit compared with placebo, which is at variance with a positive naltrexone effect being reported in the COMBINE Study. A secondary comparison between both studies showed better overall treatment outcomes in PREDICT, although these patients had been more severely affected than their COMBINE counterparts. The divergence in results may be attributable to basic differences in the treatment environments (such as in-patient pre-treatment versus primary outpatient care). We suggest that identically designed RCTs conducted in different parts of the world may help improve the external validity of RCTs. This approach could be called ‘comparative efficacy research’.
First published 12 December 2012
Gesehen am: 28.05.2014